2019
DOI: 10.15585/mmwr.ss6810a1
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Excess Deaths from the Five Leading Causes of Death in Metropolitan and Nonmetropolitan Counties — United States, 2010–2017

Abstract: Problem/Condition: A 2017 report quantified the higher percentage of potentially excess (or preventable) deaths in nonmetropolitan areas (often referred to as rural areas) compared with metropolitan areas. In that report, CDC compared national, regional, and state estimates of potentially excess deaths among the five leading causes of death in nonmetropolitan and metropolitan counties for 2010 and 2014. This report enhances the geographic detail by using the six levels of the 2013 National Center for Health St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(93 citation statements)
references
References 4 publications
1
92
0
Order By: Relevance
“…Rural populations are uniquely at risk for COVID-19-related inequities for a variety of reasons. First, rural populations are on average, older, poorer, and have higher age-adjusted rates of underlying chronic conditions (e.g., obesity, diabetes, cancer, and respiratory illnesses) and disabilities than non-rural populations in the U.S. [ 20–24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rural populations are uniquely at risk for COVID-19-related inequities for a variety of reasons. First, rural populations are on average, older, poorer, and have higher age-adjusted rates of underlying chronic conditions (e.g., obesity, diabetes, cancer, and respiratory illnesses) and disabilities than non-rural populations in the U.S. [ 20–24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, the number of potentially excess deaths from cancer was approximately 39 000 in the United States. 7 Cancer had the lowest (9.2%) percentage of potentially excess deaths among the 5 leading causes of death, ranging from 3.2% in large central metropolitan counties (urban classification) to 21.7% in noncore counties (rural classification). These numbers mirror lower incidence and higher death rates found in nonmetropolitan counties compared with metropolitan counties.…”
mentioning
confidence: 98%
“…6 In November 2019, CDC reported that, in both rural and urban counties, the 5 leading causes of death in the United States during 2010-2017 were heart disease, cancer, unintentional injury, chronic lower respiratory disease, and stroke, which together accounted for 1.72 million deaths (approximately 61% of all deaths) in 2017. 7 Furthermore, the number of potentially excess deaths-defined as deaths among persons aged <80 in excess of the number that would be expected-differed among and within public health regions and among US states. In addition, the percentage of potentially excess deaths from the 5 leading causes of death, nationally, across public health regions, and in most states is greater in rural counties than in urban counties.…”
mentioning
confidence: 99%
See 2 more Smart Citations